Pekerja Seks Komersial - L.M. Kamaluddin Aksyah; Hasniah . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT The objective of this study is to identify and to describe the relationship between pimps and prostitutes, and also the activities of pimps and prostitutes in Pagar Seng Mandonga Kendari. Data was collected by observation techniques and interview. Data were analyzed by descriptive qualitative. The results showed that the relationship between pimps and prostitutes in Pagar Seng started on 1999 since the formation of Pagar Seng itself, that the relationship started with a relationship with the consent of both parties without a written agreement in a form of bondage and done with mutual trust and understanding which was based on the embroidery work to give satisfaction and profit on each side. Besides having a relationship between pimp and prostitute in Zinc Fence, they also had an activity where pimps activity was divided into two types; these were as a housewife and a pimp themselves in Pagar Seng. The activity of prostitute who had child in Pagar Seng was not much different from the activity of prostitutes who did not have children. The activity of prostitutes who had a companion outside of Pagar Seng was like staying at mate’s home and doing prostitution outside the Pagar Seng, while the activity of prostitutes who had a companion outside the Pagar Seng was killed with their companion. Keywords: pimp relations, commercial sex workers